2016
DOI: 10.4103/0366-6999.182841
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Fecal Microbiota at Newly Diagnosed Type 1 Diabetes in Chinese Children

Abstract: Background:Recent studies have indicated that an imbalance of gut microbiota is associated with the development of type 1 diabetes mellitus (T1DM) and there is no literature regarding it in Chinese children yet. The aim of this study was to evaluate the alteration of gut microbiota between children with newly diagnosed T1DM and healthy controls and to determine if gut microbiota could partly explain the etiology of this disease.Methods:A case-control study was carried out with 15 children with T1DM and 15 heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 27 publications
5
77
1
1
Order By: Relevance
“…In spite of the protective effect of GEN on T1D among females, increased Erysipelotrichaceae (28), and decreased Escherichia (27), Lachnoslira (25), Firmicutes (other genus) and Enterococcus (29) at the genus level suggested a pro-inflammatory status in our GEN-treated NOD females. At the order level, increased Erysipetotrichalae (28) and Clostridia (other order), and decreased Firmicutes (other order) also indicated an exacerbating effect of T1D.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In spite of the protective effect of GEN on T1D among females, increased Erysipelotrichaceae (28), and decreased Escherichia (27), Lachnoslira (25), Firmicutes (other genus) and Enterococcus (29) at the genus level suggested a pro-inflammatory status in our GEN-treated NOD females. At the order level, increased Erysipetotrichalae (28) and Clostridia (other order), and decreased Firmicutes (other order) also indicated an exacerbating effect of T1D.…”
Section: Discussionmentioning
confidence: 60%
“…3C) and six at the genus level (Fig. 3D) were significantly increased following GEN treatment, suggesting a pro-inflammatory effect (25, 27-29). In addition, we have found that two diets used in this study had a differential effect (indicated by α-diversity, β-diversity, and taxonomy) on gut microbiome in VH females, which is in agreement with previous literatures (30).…”
Section: Resultsmentioning
confidence: 91%
“…In an interesting Chinese study, the faecal samples of children with T1DM were lower in abundance of bacteria than healthy controls, in particular Intestinimonas, a newly isolated Gram-positive and anaerobic bacteria producing butyrate. Comparatively, an increase of Blautia was found in these patients [46].…”
Section: Microbiome and Autoimmune Diseasesmentioning
confidence: 71%
“…48 Type 1 diabetes subjects show altered composition and diversity of their gut microbiome. Different clinical studies [49][50][51][52][53][54][55][56][57][58][59] involving changes in the gut microbiome of T1D subjects are summarized in Table 1.…”
Section: Gut Microbiomementioning
confidence: 99%